Avaliação sistêmica do lançamento de novos produtos universitários: uma abordagem baseada no pensamento sistêmico - Paraboni, Priscila Bonalume (Universidade do Vale do Rio dos Sinos, 2013)
There are many methods for the process of new product development, which focuses, mainly, in a sequence of logical steps applied by an individual or team-based and project scope. It is understood that the current organizational context requires a process of developing products that contemplate this dynamism experienced. In this sense, this research makes the application of Systems Thinking (SENGE P. M., 2012) during the process of developing a new undergraduate technological course at Unisinos, searching for launch analysis, in time and space, identifying the systemic impacts of the new course. The research was developed in the higher education sector due to the growth of this sector in Brazil and increased competitiveness (MEC/Inep, 2012) and was applied following the logic of the Design Science Research (BAYAZIT, 2004). Was mapped the current development process of new courses in the Academic Unit of Undergraduate for understanding and identifying gaps. Herewith, the methodology of Systems Thinking and Scenarios Planning (ANDRADE, et al., 2006) was applied to a group of professors and researchers at the University who participated in the development of the Technologist Management of Industrial Production course. The research presents a set as an artefact of robust strategies and conditionals apply to the University regardless of the scenario that will be set up.
Keywords: Pensamento sistêmico; Universidade; Desenvolvimento de novos cursos; Systems thinking; University; New courses development; ACCNPQ::Engenharias::Engenharia de Produção